Topical Polymyxin‐Trimethoprim Prophylaxis May Decrease the Incidence of Driveline Infections in Patients With Continuous‐Flow Left Ventricular Assist Devices. Issue 2 (21st April 2016) - Durand, Marlene L.; Ennis, Stephanie C.; Baker, Joshua N.; Camuso, Janice M.; McEachern, Kathleen M.; Kotton, Camille N.; Lewis, Gregory D.; Garcia, Jose P.; MacGillivray, Thomas E.
Abstract: This retrospective cohort study evaluated the effect of topical polymyxin‐trimethoprim (poly) prophylaxis on the incidence of driveline infections (DLIs) in patients with continuous‐flow left ventricular assist devices. All 84 cases implanted 2005–2014 with device support ≥30 days were reviewed; support ranged 1 m–5.2 yrs. Beginning 2008, poly was applied to the exit site with dressing changes. Sixty‐five patients received poly (poly group) for duration of follow‐up, 19 did not (no‐poly); group baseline characteristics were similar. No patient developed side effects from poly. Nineteen DLIs (10 in no‐poly) occurred; not using poly was a risk factor. 89% of poly group DLIs were superficial, 4 were culture‐negative. DLI‐related bacteremia occurred in 11% of no‐poly group and 0% of poly group. Compared with no‐poly, poly group demonstrated improved freedom from DLI by Kaplan‐Meier analysis ( P  < 0.0001) and a 75% lower overall and 95% lower deep DLI incidence ( P  ≤ 0.001). Deep DLIs occurred in 31.6% of no‐poly vs. 1.5% of poly patients ( P  = 0.0004), although mean support duration (1 yr) and % support >1 yr (38%) were similar. These findings, which should be confirmed with larger comparative studies, suggest that topical polymyxin‐trimethoprim prophylaxis may be effective in preventing DLIs.